Knowledge village capital framework in the Indian context. (1st January 2013) - Batra, Surinder; Payal, Ruchi; Carrillo, Francisco Javier
Knowledge-based development (KBD) has attracted increasing attention over the past years, particularly as applied to countries, regions and cities. A distinctive approach has been to assess and develop the social knowledge base through a knowledge capital framework. This paper explores the development of a knowledge capital framework for Indian villages. The literature on KBD has been studied and the relevance and applicability of these concepts has been examined in the context of socio-economic conditions in the villages of the country. An initial knowledge village capital framework has been developed and an exploratory factor analysis has been then conducted to test the initial framework after collecting data from 280 villages of the country. The paper concludes with a discussion on the expected value addition from this framework by expanding the realm of KBD studies into the substantial village level of analysis.